2019
DOI: 10.23941/ejpe.v12i1.377
|View full text |Cite
|
Sign up to set email alerts
|

On the Practical Impossibility of Being Both Well-Informed and Impartial

Abstract: Adam Smith argued that the ideal moral judge is both well-informed and impartial. As non-ideal moral agents, we tend only to be truly well-informed about those with whom we frequently interact. These are also those with whom we tend to have the closest affective bonds. Hence, those who are well-informed, like our friends, tend to make for partial judges, while those who are impartial, like strangers, tend to make for ill-informed ones. Combining these two traits in one person seems far from straightforward. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Collins (2004) has advanced a distinction between contributory and interactional expertise that takes a different view: that contributory expertise, the ability to write an article, is basic, and interactional expertise, the ability to understand it and comment on it, with the implication that the person who possesses contributory expertise has the capacities of the interactional expert and something more. But Sivertsen (2019) has recently shown that there is a cognitive science basis for thinking that the capacity to judge and the capacities characteristic of the specialist are not only distinct but conflicting. This was a point also made by James Bryant Conant in his writings on science, which noted the tendency for scientists to fall in love with their own ideas.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Collins (2004) has advanced a distinction between contributory and interactional expertise that takes a different view: that contributory expertise, the ability to write an article, is basic, and interactional expertise, the ability to understand it and comment on it, with the implication that the person who possesses contributory expertise has the capacities of the interactional expert and something more. But Sivertsen (2019) has recently shown that there is a cognitive science basis for thinking that the capacity to judge and the capacities characteristic of the specialist are not only distinct but conflicting. This was a point also made by James Bryant Conant in his writings on science, which noted the tendency for scientists to fall in love with their own ideas.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%